Community structure of plankton in Whiteleg Shrimp, Litopenaeus vannamei (Boone, 1931), pond ecosystem - ZAKIYYAH NUR INAYAH; MUHAMMAD MUSA; DIANA ARFIATI; RIZKY KUSMA PRATIWI (Society for Indonesian Biodiversity, 2023)
Abstract. Inayah ZN, Musa M, Arfiati D, Pratiwi RK. 2023. Community structure of plankton in Whiteleg Shrimp, Litopenaeus vannamei (Boone, 1931), pond ecosystem. Biodiversitas 24: 4008-4016. Plankton in shrimp farming can be used to maintain the balance of the pond ecosystem. The purpose of this study is to analyze the plankton community in the whiteleg Litopenaeus vannamei shrimp pond ecosystem. This research was conducted in January-April 2023 and it is a descriptive study using a survey method. The research location is in an intensive whiteleg shrimp aquaculture pond in Probolinggo, East Java. The results showed that the plankton found in whiteleg shrimp ponds consisted of phytoplankton and zooplankton. The phytoplankton found consisted of 4 phyla with 18 genera, while zooplankton consisted of 3 phyla with 8 genera. Phytoplankton phylum consists of Bacillariophyta, Chlorophyta, Cyanophyta and Dinophyta, while zooplankton consists of Arthropoda, Ciliophora and Rotifera phyla. The highest total abundance of phytoplankton was 8,192,370 cells/L, while zooplankton was 55,121 cells/L. The highest abundance of phytoplankton was Oocystis (Chlorophyta) of 8,094,015 cells/L, while zooplankton, namely Euplotes (Ciliophora) was 40,154 ind/L. The index of diversity, uniformity and dominance of phytoplankton ranged from 0.05-1.76, 0.02-0.65 and 0.38-0.99, respectively. Zooplankton has diversity, uniformity and dominance indices ranging from 0-2.03, 0-1 and 0.27-1, respectively.